NOUNSENSE: Boosting ESL students' language skills through board games / Amirah Athirah Amir Yazid ... [et al.] - Amir Yazid, Amirah Athirah; Bazlan, Anis Shahira; Amir Yazid, Amir Ashraf; Mohammad Omar, Nur Diana Nabila; Mohd Raslan, Nur Dayana (2023)
Board games have been widely used in ESL classrooms as teaching aids. This research is aimed at studying the students’ understanding of nouns as well as their interpretation of graphics based on the board game. This study’s focus group is among undergraduate students focusing on ESL classroom settings. Nounsense is a board game created and curated by a team of researchers focusing on enhancing the vocabulary of nouns as well as allowing students to differentiate between common nouns and proper nouns. The game “Nounsense'' will be introduced in the ESL classroom as an aid as well as a test for students’ understanding of common nouns and proper nouns. The board game consists of 30 cards on a deck with mixtures of common nouns and proper nouns. Nounsense uses nouns that are widely used in Malaysia to highlight the Malaysian culture as well as the diversity of Malaysia. This study will also analyze how well the students can identify according to the graphics as well as interpret whether the shown graphic is a common noun or a proper noun. Vocabulary learning is considered an essential part of foreign language learning as the meanings of new words are very often emphasized, whether in books or in classrooms (Hadi, Izaah, & Larasati, 2021). It is crucial to include the usage of Nounsense in the ESL classroom to test the understanding of nouns among students in the ESL classroom as well as introduce Malaysian cultures through Nounsense. Incorporating culture as well as learning English in the ESL classroom, Nounsense has the novelty of creating a fun, interactive, and educational environment for undergraduate students to learn nouns in the ESL classroom as well as learn Malaysian culture through graphics.